Carbon templated strategies of mesoporous silica applied for water desalination: A review - Elma, M. (Elsevier Ltd, 2020)
Porous materials have attracted attention in many practical fields, including for water desalination. Carbon templated is an attractive method in enhancing the properties of mesoporous silica materials used as membrane materials. This review mainly focuses on the strategies of carbon templates of mesoporous silica materials essentially applied for water desalination. Numerous strategies for carbon templated mesoporous silica are briefly discussed. In addition, most carbon-silica based membranes for desalination are detailed and their performances are discussed. Moreover, application of carbon-silica templates for wetland saline water desalination are also discussed in great detail. The comparison between carbon-silica based materials and silica-based membranes of recent techniques, fabrication, trend, application and operation condition for further improvement of membrane performance are also thoroughly reviewed. Â© 2020 Elsevier Ltd